(untitled) (Colombia Medica, 1986)
This paper documents drug use in high school through a probabilistic sample of 52 schools, including 1937 students in Cali, Colombia. Males tend to use more drugs than females; the reported use during the last month for the sample was 2.6% for cocaine, 3.0% for coca paste, and 4.1% for marihuana. Fifteen questionnaires were produced and validated to identify aspects related to drug use. Affectionate relationships among parents and youngsters diminish the risk of drug use; parental time, effectively utilized with youngsters, appears to be essential for protection against drug use. A consistent, disciplinarian, and alert attitude about outside activities is associated with non-drug use. Paternal disinterest and permissiveness are significantly associated with male drug use, whereas maternal disinterest and lack of affection are significantly associated with drug use among women. The preventive implications of these findings are clear; the factors associated with drug use in these populations will be included in a risk scale (now in the final phase of development) that will allow the identification of youngsters at risk of becoming drug users.